A Novel Levulinate‐Based Highly Specific Colorimetric Fluorescent Probe for Bisulfite Detection in Live Cells and Zebrafish. Issue 14 (8th April 2022) - Zhao, Zhenhua; Xing, Liting; Feng, Quanlin; Han, Lin
Abstract: Bisulfite (HSO3 − ) is associated with many physiological processes in living systems. High concentration of HSO3 − may lead to many diseases. Herein, a simple levulinate‐based colorimetric fluorescent probe for HSO3 − detection was designed and synthesized. The probe showed high selectivity for HSO3 − detection with color changes from light pink to deep pink. Under the optimal test conditions, there is a good linear relationship between fluorescence intensity and concentrations of HSO3 − in the range of 0–50 μM with detection limit of 1.04 nM. In addition, the probe was successfully applied to monitor HSO3 − in living cells and zebrafish, which proved that the probe can be used to detect HSO3 − in living systems. Abstract : A simple levulinate‐caged rhodol as colorimetric fluorescent probe for visualizing and monitoring HSO3 − in living system was designed and synthesized. The probe provides a reliable method to quantitatively detect HSO3 − with high specificity and sensitivity, good linearity, and lower detection limit. Moreover, the probe was successfully applied to monitor HSO3 − in live cells and zebrafish. The probe was proved to be a useful tool in biological applications.